Reappraisal of Oral Steroid Therapy for Myasthenia Gravis - Imai, Tomihiro; Suzuki, Shigeaki; Nagane, Yuriko; Uzawa, Akiyuki; Murai, Hiroyuki; Utsugisawa, Kimiaki (Frontiers in Neurology, 2020)
Treatment with oral corticosteroids at high doses with an escalation and de-escalation schedule is effective against myasthena gravis (MG). In fact, the use of corticosteroids has led to a reduction in mortality to below 10% after the 1960s. However, long-term use of oral steroids above a certain dosage level is known to cause a number of problems. In 2014, the Japanese clinical guidelines for MG proposed that the first goal in MG treatment (treatment target) should be set at minimal manifestations (MM) with oral prednisolone (PSL) 5 mg/day or below, and that treatment strategies should strive to attain this level as rapidly as possible. In 2015, a multicenter, cross-sectional study revealed that higher PSL dose and longer PSL treatment do not ensure better outcome. In the absence of good response, the PSL dose should be decreased by combining with modalities such as plasma exchange/plasmapheresis and intravenous immunoglobulin (fast-acting treatments). In 2018, we conducted a multicenter, cross-sectional study in a large population of Japanese patients with generalized MG, aiming to elucidate the correlation between oral PSL regimens and achievement of treatment goals. The ORs for low vs. high dose to achieve treatment goals at 1, 2, and 3 years were 10.4, 2.75, and 1.86, respectively, whereas the corresponding ORs for low vs. medium dose were 13.4, 3.99, and 4.92. Early combination with fast-acting therapy (OR 2.19 at 2 years, 2.11 at 3 years) or combination with calcineurin inhibitors (OR 2.09 at 2 years, 2.36 at 3 years) were also positively associated with achieving treatment goals. These results indicate that early combination of low-dose PSL regimens with other therapies is the key for early achievement of treatment goals in generalized MG. However, even with this regimen, ~35% of patients did not achieve the treatment target after 3 years. These results suggest the limitation of the current oral corticosteroid therapy. We need to develop new treatment options to increase the rate of satisfactory outcome.